Peran Stakeholder sebagai Aktor Kebijakan Pemberdayaan Kelompok Perempuan “Sepakat” melalui Potensi Lokal di Kabupaten Aceh Barat Daya - Safrida Safrida; Afrizal Tjoetra; Rachmatika Lestari; Nila Safrida (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
In Aceh Barat Daya District, this essay examines the role of stakeholders as players in empowering the women's group "Agreed" through regional potential. This study employs a case study methodology and a qualitative research design. Data was gathered by observation, interviews, and documentation. Triangulation validity, reliability, and interactive analysis models were then used to analyze the data. The study's findings demonstrate that stakeholders have played a significant role as policy actors for empowerment programs since the implementation of the Participatory Missile Appraisal (PRA) and Participation Assessment Plan (MPA) processes, which prioritize community involvement. supported by the application of the ideas of corporate development, institutional development, and human development. However, it is clear from the existence of unresolved business issues like seasonal business, the lack of specialized training and enrichment of product innovation for groups, as well as the inability to organize businesses, that the needs of the "Agreed" women's group have not been met in practice as expected. So, solid cooperation between policy actors is needed in carrying out empowerment and more efforts to evaluate implementation to assess the level of success of the program being implemented